Efektivitas Cyber Counseling untuk Meningkatkan Self Regulated Learning Mahasiswa - Putri Harahap, Ade Chita; Putra Sinaga, M. Harwansyah; Br. Tarigan, Nabiilah Husnaa (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2023)
This research aims to determine the effectiveness of cyber counseling to improve students' self-regulated learning (SRL). This research method uses a pretest-posttest control group design. Data was collected by using self-regulated learning scale, which had been validated and its reliability had been measured. The research population were 195 students with 8 students selected using purposive sampling as its sample. The data analysis technique uses the t-test. The results of this research reveal that cyber counseling is effective in improving students' SRL as seen from the difference in the average of SRL’s score between students who were given cyber counseling and students who were not given cyber counseling.